Effect of knowledge management practices on business performance in Bangladesh pharmaceutical industry - Haque, Mahbubul; Islam, Rafikul (UiTM Terengganu, 2012)

(untitled)
During the past decade, the area Knowledge Management (KM) has drawn considerable attention from researchers. This is due to the fact that firms’ performances are increasingly hinge upon managing knowledge of their employees rather than managing only physical facilities and resources. The present study intends to investigate the effect of KM practices on business performance in Bangladesh Pharmaceutical industry. Factor analysis has identified three factors of KM, namely organization culture, IT infrastructure and performance measurement. Structural Equation Modelling application has found that IT infrastructure and performance measurement have positive impact on business performance, while no significant relationship was observed between organization culture and business performance. Managerial implications of the findings are put forward.